Effects of an Intervention with educational phone calls to improve adherence and metabolic control in people with type 2 diabetes mellitus: A randomized clinical trial - De La Cruz-Saldaña, Tania (2021)
Introduction: Information and communication technologies can help us improve metabolic control and adherence in people with type 2 diabetes mellitus (DM2). Objective: To evaluate the effects of an intervention with telephone calls in outpatients with poorly controlled DM2 in a hospital in Peru. Material and Methods: Randomized clinical trial. We included adults with DM2 with poor glycemic control, who were randomized to the control group (usual care) or to the intervention group (usual care plus a telephone intervention every two weeks for three months). The primary outcome was a ≥ 1% reduction in glycosylated hemoglobin at three months. Results: 94 participants were recruited (47 in each group). Mean age was 59.8 years (SD: 10.2), 69.2 % were women. At three months, only 14/47 participants in the control group and 13/47 participants in the intervention group had HbA1c measurement. Among these, the percentage of those who achieved a ≥ 1% decrease in HbA1c was 35,7% (5/14) in the control group and 53,8% (7/13) in the intervention group (RR: 0,72, 95% CI: 0,35-1,47). No differences were found in adherence to treatment between groups. Conclusions: No statistically significant differences were found for the outcomes of interest. This is possibly due to the low percentage of participants who were able to complete follow-up. Innovative solutions are needed to improve the control of people with DM2.